Reversibility of impaired nasal mucociliary clearance in smokers following a smoking cessation programme - Cipulo Ramos, Ercy Mara [UNESP] (2011)
Background and objective: Smoking cessation (SC) is recognized as reducing tobacco-associated mortality and morbidity. The effect of SC on nasal mucociliary clearance (MC) in smokers was evaluated during a 180-day period. Methods: Thirty-three current smokers enrolled in a SC intervention programme were evaluated after they had stopped smoking. Smoking history, Fagerstrom's test, lung function, exhaled carbon monoxide (eCO), carboxyhaemoglobin (COHb) and nasal MC as assessed by the saccharin transit time (STT) test were evaluated. All parameters were also measured at baseline in 33 matched non-smokers. Results: Smokers (mean age 49 +/- 12 years, mean pack-year index 44 +/- 25) were enrolled in a SC intervention and 27% (n = 9) abstained for 180 days, 30% (n = 11) for 120 days, 49.5% (n = 15) for 90 days or 60 days, 62.7% (n = 19) for 30 days and 75.9% (n = 23) for 15 days. A moderate degree of nicotine dependence, higher education levels and less use of bupropion were associated with the capacity to stop smoking (P < 0.05). The STT was prolonged in smokers compared with non-smokers (P = 0.002) and dysfunction of MC was present at baseline both in smokers who had abstained and those who had not abstained for 180 days. eCO and COHb were also significantly increased in smokers compared with non-smokers. STT values decreased to within the normal range on day 15 after SC (P < 0.01), and remained in the normal range until the end of the study period. Similarly, eCO values were reduced from the seventh day after SC. Conclusions: A SC programme contributed to improvement in MC among smokers from the 15th day after cessation of smoking, and these beneficial effects persisted for 180 days.